FROM DIALOGUE TO COOPERATION: STATE-CONFESSIONAL RELATIONS IN REPUBLIC OF BELАRUS - E. S. Kuzmitovich (Наука и техника)
The paper is devoted to the problem of state-confessional relation in theRepublicofBelarusat present stage and considers a religious situation in the country, attitude of the State to conventional religious organizations and Christian human values. The presented concrete material reveals the essence of these relations and main tendency of their development, namely: from dialogue to cooperation and social partnership.